The secrets of menstrual blood: emerging frontiers from diagnostic tools to stem cell therapies - Feng, Yige; He, Yujie (Frontiers in Cell and Developmental Biology, 2025)
Menstrual blood (MB), a biofluid rich in diverse cell types and biomolecules, has emerged as a vital resource for investigating female reproductive health and diseases because of its unique composition and noninvasive accessibility. This review explores the potential of MB in medical research and clinical applications, focusing on its diagnostic and therapeutic prospects. For disease diagnosis, MB offers a noninvasive sampling method for identifying biomarkers in endometriosis, cervical cancer, and other gynecological conditions. Therapeutically, stem cells derived from MB (menstrual blood-derived stem cells, MenSCs) exhibit pluripotency, high proliferative capacity, and low immunogenicity, positioning them as promising candidates in regenerative medicine. Preclinical and clinical studies have demonstrated the efficacy of MenSCs in treating infertility, premature ovarian insufficiency, intrauterine adhesions, hepatic disorders, cutaneous injuries, and neurological diseases. MenSCs also exert therapeutic effects through paracrine mechanisms by releasing cytokines and exosomes that modulate immunity, attenuate inflammation, and promote tissue repair. Despite existing challenges, MenSCs hold substantial promise for developing novel therapeutic strategies across multiple disease domains.